Nutrient Composition Analysis of Maize Hybrids Affected by Different Nitrogen Fertilisation Systems - Csaba Bojtor; Seyed Mohammad Nasir Mousavi; Árpád Illés; Farid Golzardi; Adrienn Széles; Atala Szabó; János Nagy; Csaba L. Marton (Plants, 2022)
Maize is one of the most widely used plants in the agricultural industry, and the fields of application of this plant are broad. The experiment was conducted at the Látókép Crop Production Experimental Station of the University of Debrecen, Hungary. Three mid-ripening maize hybrids with different FAO numbers were used in the present study. The effects of different nitrogen supplies were examined as a variable rate of abiotic stress and the interrelationship among the essential nutrients through the nutrient acquisition and partitioning of the different vegetative and generative plant parts. The results showed that NPK application compared to the control treatment (no fertilizer application) increased DM in all tissues of maize, while increasing nitrogen application from 120 to 300 kg ha−1 had no significant effect on this trait. The highest protein content was obtained with the nitrogen application of 120 kg ha−1, and the higher nitrogen fertilizer application had no significant effect on this trait. Seeds and leaves had a maximum zinc and manganese value in terms of nitrogen content (protein). Dry matter was positively correlated with nitrogen, potassium, and manganese content, while the dry matter had a negative correlation with nickel content. In general, to achieve a maximum quantitative and qualitative yield, it is recommended to use NPK fertilizer with a rate of 120 kg ha−1 N for maize cultivation.